2014
DOI: 10.1371/journal.pone.0093394
|View full text |Cite
|
Sign up to set email alerts
|

New Classes of Mind Bomb-Interacting Proteins Identified from Yeast Two-Hybrid Screens

Abstract: Notch signaling pathway defines an evolutionarily conserved mechanism in cell-fate determination in a broad spectrum of developmental processes through local cell interactions. mind bomb (mib) encodes an E3 ubiquitin ligase that is involved in Notch activation through Delta ubiquitylation and internalization. To further dissect the function of Mib, two yeast two-hybrid screens for zebrafish Mib/Mib2-binding proteins with different strategies have been performed. 81 putative interesting proteins were discovered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 77 publications
4
24
0
Order By: Relevance
“…Recent proteomics and yeast two-hybrid studies have hinted at a centrosome-associated function for the E3 ubiquitin ligase Mib1 (Akimov et al, 2011;Jakobsen et al, 2011;Tseng et al, 2014). In line with these results, we found that Mib1 colocalizes with PCM-1 (Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Recent proteomics and yeast two-hybrid studies have hinted at a centrosome-associated function for the E3 ubiquitin ligase Mib1 (Akimov et al, 2011;Jakobsen et al, 2011;Tseng et al, 2014). In line with these results, we found that Mib1 colocalizes with PCM-1 (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Such conditions are known to occur in breast cancer as well as other tumor types (Chng et al, 2008;Macmillan et al, 2001;Mason et al, 2014;van de Vijver et al, 2002). Specifically, we propose that SCF b-TrCP is the major E3 ligase controlling steady-state Plk4 levels under physiological conditions (Cunha-Ferreira et al, 2013; Cunha-Ferreira et al, , and the centriole maker Cep135 (blue).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In our previous study (12), Choe et al presented evidence for Mib1 interaction with several other kinases in addition to proteins involved in membrane trafficking, the UPS, the cytoskeleton, and cell adhesion. These categories of Mib1 protein interaction were reiterated and elaborated upon by a yeast two-hybrid screen, revealing 81 putative binding partners for Mib1 and Mib2 (19). The present study reports an even larger list of potential Mib1 binding partners from adult rat brain, further expanding the Mib1 interaction network, reinforcing several pathways mentioned above, and introducing more components.…”
Section: Discussionsupporting
confidence: 56%
“…Mib1 was found to mediate the degradation of survival motor neuron 1 (SMN1), which contributes to spinal muscular atrophy (17). Mib1 was reported to be essential for Wnt3A activation of beta-catenin signaling through the receptor RYK (18), and a recent yeast two-hybrid screen indicated that Mib1 interacts with 81 candidate proteins beyond the canonical Notch pathway (19). The ongoing identification of new Mib1 interaction partners and functions underscores the need to characterize the Mib1 interactome en masse with high confidence.…”
mentioning
confidence: 99%